AGAMA KHONGHUCU DAN BUDDHA DALAM LINTASAN SEJARAH KOREA - Zainal Abidin Eko Putro; Cahyo Pamungkas (Jurnal Kajian Wilayah, 2017)
South Korean society has a plural society with its different religious background. Khonghucu (Confucianism) and Buddhism have grown in the country for the last several centuries. Khonghucu teaches philosophy and thingking about politics and culture which form identity and ethic of Korean society. Likewise, Buddhism has a role in establishing basic identity and culture of Korean society. Other religions such as Catholic, Islam, Protestant, and shamanism are also followed by Korean. This article tries to respond the question about religious environment among Korean society, especially the question for the ground of Confucianism and Buddhism in Korean history. This article is resulted from a desk literature research which also aims at describing the current development of Confucianism and Buddhism and their role in forming culture as well as identity of Korean people.Keywords: Confucianism, Buddhism, shamanism, Xu she scripture, and mass culture.AbstrakMasyarakat Korea Selatan merupakan masyarakat yang heterogen dari sisi agama. Agama Khonghucu dan Agama Buddha telah berkembang di Korea sejak berabad lampau. Agama Khonghucu sangat mengandung unsur-unsur filsafat pemikiran, politik, dan kebudayaan yang berakar dan berpengaruh ke dalam pembentukan etika dan identitas bangsa Korea. Agama Buddhajuga berperan dalam pembentukan dasar-dasar identitas dan kebudayaan Korea. Selain Agama Kristen, Islam dan Katholik, agama setempat atau shamanisme juga tetap dipeluk sebagian masyarakat Korea Selatan. Artikel ini bertujuan untuk menjawab pertanyaan bagaimanakah situasi kehidupan beragama di Korea Selatan dan bagaimanakah kedudukan Agama Khonghucu dan Buddha dalam sejarah perjalanan bangsa Korea. Tulisan yang dihasilkan dari penelitian literature ini ini juga dimaksudkan untuk mendeskripsikan bagaimanakah kondisi Agama Khonghucu dan Buddha di Korea pada masa kini dan bagaimana perannya dalam membentuk kebudayaan dan identitas nasional Bangsa Korea.Kata Kunci: Agama Khonghucu, Agama Buddha, shamanisme, teks-teks Xu she, dan budaya massa.